Diversifying crops improves system productivity and resilience for smallholder farmers in rainfed drylands - Devkota Wasti, Mina Kumari; Nangia, Vinay (International Center for Agricultural Research in the Dry Areas, 2022)
Diversifying crops improves system productivity and resilience for smallholder farmers in rainfed drylands.